2016
DOI: 10.1007/s12291-016-0575-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bioflavonoid Quercetin on Expression of Urea Cycle Enzymes, Astrocytic and Inflammatory Markers in Hyperammonemic Rats

Abstract: This study evaluates the role of quercetin on the expression of urea cycle enzymes, astrocytic, neuronal and inflammatory markers in hyperammonemic rats. Hyperammonemia (provoked by intraperitonial injections of (ammonium chloride-100 mg/kg b.w for 56 days), showed diminished expression of urea cycle enzymes [carbamyl phosphate synthetase-1 (CPS-1), ornithine transcarbamylase (OTC), argininosuccinate synthetase (ASS) and arginase (ARG)] in liver and decreased expression of neuronal and astrocytic markers-gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…Next, we confirmed that QUE suppressed IL-1b-induced senescence and the expression of SASP factors, such as MMP-3, MMP-13, IL6 and IL8. Similar to our results, other studies also showed that the protein levels of MMP-3 and MMP-13 could be suppressed by QUE in chondrocytes 30 ; several articles showed that QUE downregulated the production of IL-6 at different levels in hepatocytes, astrocytes and neurons 39 . Salminen et al demonstrated that the NF-kB pathway is a crucial regulator of the expression of SASP-related genes in senescent cells 25 .…”
Section: Discussionsupporting
confidence: 91%
“…Next, we confirmed that QUE suppressed IL-1b-induced senescence and the expression of SASP factors, such as MMP-3, MMP-13, IL6 and IL8. Similar to our results, other studies also showed that the protein levels of MMP-3 and MMP-13 could be suppressed by QUE in chondrocytes 30 ; several articles showed that QUE downregulated the production of IL-6 at different levels in hepatocytes, astrocytes and neurons 39 . Salminen et al demonstrated that the NF-kB pathway is a crucial regulator of the expression of SASP-related genes in senescent cells 25 .…”
Section: Discussionsupporting
confidence: 91%